Respostas fisiológicas e mecânicas provocadas por protocolos de treinamento com diferentes durações da repetição no exercício supino - Hugo Cesar Martins Costa (2009)
The aims of this study were: a) to compare the acute effect of two training protocols with different durations of repetition on physiological responses (electromyographic signal amplitude and blood lactate concentration); b) to verify the level of correlation between physiological and mechanical responses produced by the resistance training protocols. Nineteen men (24,9 ± 4,2 yr), with at least 6 months of recreational strength training experience participated in this study. Two training protocols were carried out, consisting of three sets of six repetitions, 60% of 1RM, three minutes of rest interval between each set. In each training protocol was used a specific duration of repetition (4s or 6s) controlled by a metronome. To avoid order effects, the protocol to be performed was assigned to the subjects in a randomized and balanceddesign. The electromyographic signal amplitude of concentric and eccentric muscle actions (pectoralis major and triceps brachii muscles) was quantified by the integral of the rectified electromyographic signal (iEMG) obtained in each set of the training protocols. Blood samples were collected at rest and one minute after all three sets and then stored for later measurement of lactate concentration. During the training protocols, a photoelectric displacement sensor attached to the bar of the smith machine made possible the calculation of mechanical variables work, power and impulse. Both training protocols increased the iEMG of concentric actions in the course of the sets and the protocol 6s showed higher values of the muscular activation than the protocol 4s. With respect to pectoralis major eccentric action, there was an increase in iEMG during the sets only in the protocol 6s. Additionally pectoralis major eccentric muscle activation in the 3rd set of the protocol 6s was higher than in the protocol 4s. To the triceps brachii muscle, although the protocolsincreased the iEMG of eccentric actions, there were no differences on muscular activation between the training protocols. Both training protocols increased the blood lactate concentration during the sets, with higher values found in the protocol 6s. There were no significant correlations between the mechanical variables and the electromyographic signal amplitude, but there were significant correlations between mechanical variables and the blood lactate concentration (r = 0,49 a 0,74). The results of this study demonstrate that although a higher duration of repetition increases the electromyographic signal amplitude while performing a training protocol in the bench press exercise, for eccentric actions, this behavior may depend on the muscle group analyzed. In addition, higher duration of repetition increases the blood lactate concentration after each set of training protocol. Finally, low to moderate levels of correlation were found between mechanical variables and blood lactate concentration, and the values of the correlation are influenced by the characteristic of the training protocol used.